Febrile adults presenting to the emergency department: outcomes and markers of serious illness. Issue 2 (26th February 2004) - Knott, J C; Tan, S-L; Street, A C; Bailey, M; Cameron, P
Abstract : Objectives: To determine outcomes and markers of serious illness for febrile patients presenting to an adult emergency department. Methods: A prospective cohort study of patients presenting to the emergency department with a temperature ⩾38°C. Medical staff obtained demographic data and risk factor profiles while assessing each febrile patient. All were followed up to determine death, admission to intensive care, length of stay in hospital, or subsequent admission to hospital within 30 days. Univariate and multivariate analysis determined which factors were markers of serious illness. Results: For febrile adults admitted to hospital 3.0% died, 6.1% were admitted to intensive care, median length of stay in hospital was 7.2 days. Independent risk factors were—death: age (OR = 1.04), respiratory rate (OR = 1.06), white cell count (OR = 1.02), cardiac disease (OR = 3.3), and jaundice (OR = 21.4). Admission to intensive care: respiratory rate (OR = 1.1), pulse rate (OR = 1.03), and jaundice (OR = 5.1). Increased length of hospital stay: age (p<0.01), jaundice (p<0.01), respiratory rate (p = 0.01), focal neurological signs (p = 0.01), and changed mental state (p = 0.04). For febrile adults sent home 7.9% required admission to hospital within 30 days. Risk factors were respiratory rate (OR = 1.2), being female (OR = 5.36), malignancy (OR = 15.3), and cardiac disease (OR = 19.7). Initially having no focus of infection was protective (OR = 0.13). No febrile patient sent home from the emergency department died or required admission to intensive care. Conclusions: Few febrile adults presenting to the emergency department suffer an adverse outcome suggesting effective risk stratification is occurring. The identification of factors associated with adverse events may further improve this process.